2000
DOI: 10.1590/s0100-879x2000000700003
|View full text |Cite
|
Sign up to set email alerts
|

Structural, functional and immunological studies on a polymeric bacterial protein

Abstract: The characterization of proteins from Brucella spp, the causative agent of brucellosis, has been the subject of intensive research. We have described an 18-kDa cytoplasmic protein of Brucella abortus and shown the potential usefulness of this protein as an antigen for the serologic diagnosis of brucellosis. The amino acid sequence of the protein showed a low but significant homology with that of lumazine synthases. Lumazine is an intermediate product in bacterial riboflavin biosynthesis. The recombinant form o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The results also demonstrate that BLS is a strong B immunogen which, due to its structural characteristics (6,10), could be used to engineer chimerical immunogens able to display predefined peptides on the same molecular scaffold.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The results also demonstrate that BLS is a strong B immunogen which, due to its structural characteristics (6,10), could be used to engineer chimerical immunogens able to display predefined peptides on the same molecular scaffold.…”
Section: Discussionmentioning
confidence: 74%
“…Yet the high immunogenicity of BLS (due to the repetitiveness and order of surface epitopes) can be exploited to improve the immunogenicity of foreign epitopes, as has been described elsewhere (27). Interestingly, X-ray structural studies of rBLS (6,10) showed that is possible to insert foreign peptides at the amino terminus without disrupting its general folding. These peptides could be presented to the immune system in a polymeric way and in the context of a high specific immune response.…”
Section: Discussionmentioning
confidence: 99%
“…In some bacteria, yeast, and plants, this protein forms pentamers (Baldi et al 2000;Meining et al 2000), but in other species these pentamers are further assembled into capsids, namely, in B. subtilis (Ladenstein et al 1994) and Aquifex aeolicus (Zhang et al 2001). The capsids from the latter system, termed AaLS, can be expressed and purified from E. coli; they assemble, in vitro, into compartments either 16 or 30 nm, depending on pH and buffer conditions (Zhang et al 2006a).…”
Section: Lumazine Synthasementioning
confidence: 99%
“…Ba is one of the intracellular bacterial species responsible for brucellosis, a chronic infectious disease handling a significant global impact [ 1 , 2 ]. This condition is multisystemic affecting different tissues and organs [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ba is one of the intracellular bacterial species responsible for brucellosis, a chronic infectious disease handling a significant global impact [ 1 , 2 ]. This condition is multisystemic affecting different tissues and organs [ 1 ]. Brucellosis has been classified by the World Health Organization as one of the seven “neglected endemic zoonotic diseases of particular interest” [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%